An S-ribonuclease binding protein EBS1 and brassinolide signaling are specifically required for Arabidopsis tolerance to bicarbonate. (9th November 2020) - Chen, Jipeng; Li, Xiaoxiao; Ye, Xiaoxue; Guo, Peng; Hu, Zhubing; Qi, Guoning; Cui, Fuqiang; Liu, Shenkui
Abstract : Alkaline soils stress plants due to high bicarbonate rather than high pH. Specific genes are required for plant tolerance to bicarbonate but not other weak acid ions. Abstract: Bicarbonate (NaHCO3 ) present in soils is usually considered to be a mixed stress for plants, with salts and high pH. NaHCO3 -specific signaling in plants has rarely been reported. In this study, transcriptome analyses were conducted in order to identify NaHCO3 -specific signaling in Arabidopsis. Weighted correlation network analysis was performed to isolate NaHCO3 -specific modules in comparison with acetate treatment. The genes in the NaHCO3 -root-specific module, which exhibited opposite expression to that in sodium acetate treatments, were further examined with their corresponding knock-out mutants. The gene Exclusively Bicarbonate Sensitive 1 ( EBS1 ) encoding an S-ribonuclease binding protein, was identified to be specifically involved in plant tolerance to NaHCO3, but not to the other two alkaline salts, acetate and phosphate. We also identified the genes that are commonly regulated by bicarbonate, acetate and phosphate. Multiple brassinosteroid-associated gene ontology terms were enriched in these genes. Genetic assays showed that brassinosteroid signaling positively regulated plant tolerance to NaHCO3 stress, but negatively regulated tolerance to acetate and phosphate. Overall, our data identified bicarbonate-specific genes, and confirmed that alkaline stress is mainly dependent on the specificities of the weak acid ions, rather than high pH.